Professional Ethics And Transparency In Msme Assistance Programs In North Sumatra - Dito Aditia Nst; Alifah Humairah; Faradiba Ulfa Purba; Biwi Cahya Wigrha; Lidia Wanti Siregar; Akmal Haidir Silalahi; Shania Gracesia Br Gintin (Universitas Muhammadiyah Palu, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a key role as the main driver of the economy in North Sumatra, especially in ensuring stability after the pandemic. Although the local government has allocated billions of rupiah for capital and infrastructure support, the implementation of these programs is still hampered by issues of professional ethics and a lack of transparency. This study aims to assess the implementation of the code of ethics and information disclosure in MSME strengthening programs in the area. Using a descriptive qualitative method, this research found significant differences between the policies established and the reality in the field. Serious issues such as allegations of misuse of grant funds for the construction of MSME Square and acts of intimidation by officials against small business owners are major obstacles. The results of this study show that the success of government assistance is not only determined by the amount of funds available, but is also greatly influenced by the integrity of employees and ease of access to information for the community. This study recommends the need for an independent monitoring system and digitization of information to restore the trust of MSME actors and ensure more inclusive and responsible economic growth.